2022
DOI: 10.3390/biom12060814
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insight into Lipid Binding and Lipid Modulation of Pentameric Ligand-Gated Ion Channels

Abstract: Pentameric ligand-gated ion channels (pLGICs) play a leading role in synaptic communication, are implicated in a variety of neurological processes, and are important targets for the treatment of neurological and neuromuscular disorders. Endogenous lipids and lipophilic compounds are potent modulators of pLGIC function and may help shape synaptic communication. Increasing structural and biophysical data reveal sites for lipid binding to pLGICs. Here, we update our evolving understanding of pLGIC–lipid interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 124 publications
1
6
0
Order By: Relevance
“…With the recent abundance of lipid-bound pLGIC structures by cryo-EM, investigation into the structural mechanisms of lipid modulation has focused on direct binding of lipids to specific sites 12,13,15,[17][18][19][20][21][22] . Structures of the 5-HT 3A receptor (5-HT 3A R), GABA A receptor, nAchR and the prototypic pLGICs, Erwinia chrysanthemi ligand-gated ion channel (ELIC) and Gloeobacter violaceus ligand-gated ion channel (GLIC), show bound phospholipids at various sites 14,19,[23][24][25][26][27][28] .…”
mentioning
confidence: 99%
“…With the recent abundance of lipid-bound pLGIC structures by cryo-EM, investigation into the structural mechanisms of lipid modulation has focused on direct binding of lipids to specific sites 12,13,15,[17][18][19][20][21][22] . Structures of the 5-HT 3A receptor (5-HT 3A R), GABA A receptor, nAchR and the prototypic pLGICs, Erwinia chrysanthemi ligand-gated ion channel (ELIC) and Gloeobacter violaceus ligand-gated ion channel (GLIC), show bound phospholipids at various sites 14,19,[23][24][25][26][27][28] .…”
mentioning
confidence: 99%
“…This not only enables the detection of the membrane-embedded organization state but also enables us to titrate in/out specific membrane constituents/properties to tease apart their role in regulating the observed oligomeric organization states. Such customizability of liposomes to mimic and modulate properties of the native membrane has already made it the vehicle of choice to study a range of functions of membrane proteins, including ion transport, , G-protein driven signaling, , and protein trafficking, , to name a few. Very recently, there has also been a steady increase in the number of CryoEM structures of membrane proteins directly from liposomes. Coupling these techniques with our liposome-nMS protocol will allow direct structural, functional, and mass spectral analysis of target membrane proteins directly from the same liposome samples.…”
Section: Discussionmentioning
confidence: 99%
“…6−8 From inducing specific functional conformational states of ion channels to regulating functional homomeric and heteromeric assemblies, there are abundant examples of this direct interaction. [2][3][4]6,9 In these cases, lipids act like endogenous ligands and modulate the structural and functional states of the protein through direct and specific binding. Alternatively, cells also organize their lipidome in a laterally heterogeneous manner to create membrane nanodomains that harbor specific biophysical properties such as membrane curvature, fluidity, tension, and so on.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuronal membrane environment plays an important role in the function of ion channels. For example, pentameric ligand-gated ion channels, such as the nicotinic acetylcholine receptors, are functionally sensitive to the lipid composition of their surrounding membrane ( Baenziger et al, 2000 ; daCosta et al, 2013 ; Ananchenko et al, 2022 ). It has also been shown that several voltage-gated ion channels are functionally affected by polyunsaturated fatty acids (PUFAs), with the presence of PUFAs altering the voltage dependence and maximal current of these channels ( Elinder and Liin, 2017 ; Tong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%